(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article presents information on the Republic of Karakalpakstan’s grassland-alluvial soils, and the impact of mineral fertilizer standards used in the short povernut rotation system on the accumulation of growth and sunflower productivity.